Knowledge and practice of feeding plate obturators among medical doctors in Kanti children’s hospital - Pathak, B; Joshi, KR; Bhattarai, S; Joshi, H (Journal of Nepalese Prosthodontic Society, 2021)
Introduction: Cleft lip and cleft palate (CLCP) affects several systems and functions of the child and result in social and psychological problems.Therefore early repair of CLCP is imperative. Every cleft center follows its own surgical treatment protocol. Before closure of palatal defects, babies with cleft palate have great difficulty in feeding. To overcome this feeding difficulties, use of special bottles, nipples, initial palatal obturator therapy are used. The first exposure of those children are primarily the medical doctors including pediatricians from where they are generally referred to the concerned speciality for repair of CLCP. The aim of this study was to assess the knowledge and practice of orofacial clefts and feeding plate obturator among medical doctors working in Kanti Children’s Hospital (KCH). Method: This was a questionnaire based survey among medical doctors working in KCH. The pretested questionnaire with 7 questions each on the knowledge and practice of feeding plate obturator was distributed among the medical doctors and data was collected. The data collected were subjected to statistical analysis using frequency of responses and percentages. Results: Of the total 57 study participants, 32 (56.1%) were males and 25 (43.9%) were females. Majority i.e. 61.4% belonged to 31-40 years age group. 91.2% study participants faced the cleft lip/ palate related feeding difficulties 0-5 times/month while 5 (8.8%) faced this condition 6-10 times/ month. Majority of the infants who were less than 28 days (43.9%) attended the OPD due to difficulty in feeding/ swallowing (57.9%) followed by regurgitation/ aspiration (22.8%). 49.1% of the participants thought feeding plate oburator as the best way to feed a cleft patient on discharge from hospital. In their clinical practice, three fourth of paticipants (70.2%) had never seen a patient with feeding plate obturator, half of the participants (50.9%) didn’t advise for feeding plate obturator for patients with cleft palate and 89.5% were not aware of the replacement of feeding plate obturator. Conclusion: There is low exposure regarding the feeding plate obturator among medical doctors in KCH which needs to be reinforced through meaningful continuing education and training programs.